Public Organization’s Dynamic Managerial Capabilities on Digital Transformation - Elyusufi, Abdul Muhaimin; Suryadi, Edi; Senen, Syamsul Hadi; Rofaida, Rofi (Universitas Dharma Wacana, 2024)
This study aims to analyse how the dynamic managerial capacity and organizational readiness of the Jambi City government affect organizational performance in the digitalization transformation of this city towards smart governance. Local governments do many things to achieve the demands of regional autonomy, regional development, especially with the use of information technology, ultimately leads to the concept of smart city with one of the indicators that becomes the main intersection is smart governance This research is a descriptive-associative quantitative study that aims to describe each variable in the model, as well as find out the relationship between several variables studied, The population in this study were all Local Government Organizations (OPD) in Jambi City as many as 30 OPDs with a sample of 149 managers which are directly implement the Smart Governance agenda. The results showed the achievement of smart governance in three aspects; excellent service, bureaucratic management and decision making. All three are supported directly or partially by the dynamic managerial abilities of the head of the office and the head of the section or unit in the OPD. However, the organizational readiness of the OPD contributes negatively, meaning that all organizational components are not ready to support the transformation of smart governance and only from key managers. This study also found that another factor that is fundamental to the implementation of smart governance is the political will of the Jambi City Regional Head